The Andean utopia - Burga, Manuel (1982)
When the European invasion of the Andean area took place in the 16th century, these territories were not an empty space nor were they an area of ​​tribal culture; on the contrary, the Europeans arrived in an area where culture had reached a high level of development with the particularity that these processes took place independently of what was happening in Europe. The historical background of the Inca Empire (just the last expression of a long historical evolution), did not go unnoticed by the conquerors. Since then, the discussion arose about how to name these men who, without being barbarians, were not Europeans either. But along with this issue, decades after the capture of Cajamarca, another question would arise: what capacity for persistence did the civilization of the vanquished have? For some, Christianization had even been too fast, but others argued that under the Christian clothing, in reality, pre-Hispanic beliefs lay beneath. Themes of the chroniclers, visitors and eradicators of colonial idolatry; subject also of contemporary anthropologists and sociologists.